1966
DOI: 10.1002/aic.690120131
|View full text |Cite
|
Sign up to set email alerts
|

Formation of interfacial area at high rates of gas flow through submerged orifices

Abstract: The interfacial area produced was correlated as a function of the physical properties of the fluids, the diameter and number of orifices per plate, and the gas flow rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1966
1966
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Similar agreement between the two injector types was found throughout the test range. It is notable that other phenomena involving gaseous injection into liquids have shown a similar lack of dependence on external injector geometry ( 9 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar agreement between the two injector types was found throughout the test range. It is notable that other phenomena involving gaseous injection into liquids have shown a similar lack of dependence on external injector geometry ( 9 ) .…”
Section: Resultsmentioning
confidence: 99%
“…X B = 0.7166B0. '689 ( Go/G,) 0.6446 (9) The multiple correlation coefficient for Equation (9) was 0.950 with an average absolute deviation between the measured and predicted values of penetration length of 11.7%. The standard deviations of the powers of B and the mass velocity ratio on the right-hand side of Equation ( 9 ) were 0.0342 and 0.0273, respectively.…”
mentioning
confidence: 94%
“…Finally, in apparent contradiction to Equation ( 1) , Abdel-aal et al (1966) carried out experiments with bubbles in which they took care to exclude scattered light from the detector and they found a relationship of the form…”
Section: The Equation Which Applies Ismentioning
confidence: 96%
“…Additionally, experiments measuring the change in mass transfer parameters due to increases in viscosity yield differing results depending upon whether the viscosity increase is caused by the addition of solids or by the addition of a high-viscosity fluid. Sharma and Mashelkar (1968) and Abdel-aal et al (1966) demonstrated an increase in a with increased viscosity for a glycerol and water mixture in a bubble column. Godbole et al (1 983) and Gollakota and Guin (1984), however, reported that a decreased with increased viscosity caused by increased solids loading.…”
Section: Discussionmentioning
confidence: 96%